2018
DOI: 10.1111/imb.12512
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference validation of detoxification genes involved in ivermectin tolerance in Drosophila melanogaster

Abstract: Previously, we observed increased transcription levels of specific cytochrome P450 monooxygenase (P450) and adenosine triphosphate binding cassette (ABC) transporter genes in human body lice, Pediculus humanus humanus, following exposure to ivermectin using the non-invasive induction assay, which resulted in tolerance. To confirm the roles of these genes in induction and tolerance, the robust genetic model insect Drosophila melanogaster was chosen. Orthologous genes corresponding to the body louse P450 (Cyp9f2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…ABCG–H genes have been suggested to contribute to insecticide detoxification as well based on the indirect finding of upregulated gene expression in response to exposure to different insecticides 21–30, 54 . Only in the case of ivermectin resistance in Drosophila flies, however, has direct genetic evidence for the contribution of an ABCG transporter to insecticide resistance been provided 31 . Therefore, we focused on TcABCG–H genes and addressed the question of whether they potentially contribute to insecticide detoxification in coleopteran species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ABCG–H genes have been suggested to contribute to insecticide detoxification as well based on the indirect finding of upregulated gene expression in response to exposure to different insecticides 21–30, 54 . Only in the case of ivermectin resistance in Drosophila flies, however, has direct genetic evidence for the contribution of an ABCG transporter to insecticide resistance been provided 31 . Therefore, we focused on TcABCG–H genes and addressed the question of whether they potentially contribute to insecticide detoxification in coleopteran species.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29][30]54 Only in the case of ivermectin resistance in Drosophila flies, however, has direct genetic evidence for the contribution of an ABCG transporter to insecticide resistance been provided. 31 Therefore, we focused on TcABCG-H genes and addressed the question of whether they potentially contribute to insecticide detoxification in coleopteran species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, although the role of Cyp6g1 in DDT resistance is established, neither is any direct role of Cyp6g2 in DDT resistance yet reported from Drosophila, nor is there direct functional evidence for enzymatic products of Cyp6g2 in DDT detoxification. However, a number of previous studies suggested that the overexpression of Cyp6g2 gene was associated with resistance to several insecticides such as imidacloprid, ivermectin, and diazinon in Drosophila 35,38,39 . Moreover, the significant overexpression of Cyp6g2 was associated with the DDT-resistant 91-R compared to susceptible strains Canton-S and 91-C 12,19,31 .…”
Section: Discussionmentioning
confidence: 99%